EFEKTIVITAS METODE SQ4R (SURVEY, QUESTION, READ, REFLECT, RECITE, REVIEW) DALAM PEMBELAJARAN MEMAHAMI TEKS FEATURE KELAS VII SMP NEGERI 1 SIDIKALANG TAHUN PEMBELAJARAN 2012/2013 - EDWARD COCO PRIYONO PARDEDE (Universitas Negeri Medan, 2012)
Effectiveness SQ4R method (Survey, Question, Read, Reflect, Recite, Review) Understanding the Text Feature in Learning Seventh Grade Students of SMP Negeri 1 Sidikalang Learning Year 2012/2013. Thesis. Indonesian Language and Literature Department. Faculty of Language and Arts. State University of Medan. 2013 This study aims to determine the effectiveness of the method SQ4R (Survey, Question, Read, Reflect, Recite, Review) in learning to understand the text feature class VII SMP Negeri 1 Sidikalang many as 253 people. Samples taken as many as 74 people from the two classes, class of 37 people to 37 people for the experiment and the control class. The method used in this study is an experimental method, which is to determine the effectiveness of the teaching methods used. Data collection tool was a written test in the form of multiple choices (multiple-choice). Learning outcomes using SQ4R (Survey, Question, Read, Reflect, Recite, Review) is in both categories with an average value of 72.97. When compared to learning by teaching methods directly in the category of simply average value of 55.10. Analysis of data management in this study using the test